Early-Onset Diabetes as Risk Factor for Pancreatic Cancer: miRNA Expression Profiling in Plasma Uncovers a Role for miR-20b-5p, miR-29a, and miR-18a-5p in Diabetes of Recent Diagnosis - Tavano, Francesca; Fontana, Andrea; Mazza, Tommaso; Gioffreda, Domenica; Biagini, Tommaso; Palumbo, Orazio; Carella, Massimo; Andriulli, Angelo (Frontiers in Oncology, 2020)
Early detection of pancreatic cancer (PanC) represents the greatest challenge to improve long-term disease survival. The high prevalence of early-onset diabetes in patients with PanC implies that recognition of recent diabetes could help identify people at high risk of developing PanC. Herein, candidate circulating microRNAs (miRNAs) associated with diabetes of recent diagnosis were screened from our previous miRNA expression profiling on 10 pools of plasma from PanC patients and non-PanC controls, both including also subjects with early- and late-onset diabetes. The droplet digital PCR (ddPCR) was used to re-test candidate miRNAs in a new independent cohort of 69 subjects (40 PanC and 29 non-PanC) with early- (17 PanC and 13 non-PanC) or late-onset (23 PanC and 16 non-PanC) diabetes, and in a control group including 100 non-diabetic healthy subjects (HS). MiRNAs plasma levels were evaluated for differences between subjects enrolled into the study and for their diagnostic performance, also compared to CA 19-9 determinations. MiR-20b-5p, miR-29a, and miR-18a-5p were selected from the previous miRNA expression profiling. The ddPCR confirmed the significant increase of miR-20b-5p and miR-29a levels in plasma from PanC patients with early- compared to those with late-onset diabetes. Conversely, the levels of miR-20b-5p, miR-29a, and miR-18a-5p in plasma were significantly higher in both PanC patients and non-PanC controls with recent-diabetes compared to HS. Although each miRNA achieved a similar diagnostic performance in distinguishing either PanC or non-PanC with early diabetes from HS (miR-20b-5p: AUC=0.877 vs. AUC=0.873; miR-29a: AUC=0.838 vs. AUC=0.810; miR-18a-5p: AUC=0.824 vs. AUC=0.875), plasma levels of miR-20b-5p achieved a higher diagnostic performance to discriminate non-PanC with early-onset diabetes from HS (AUC=0.868; SP=81%; PPV=32.1%) compared to the CA 19-9 determinations (AUC=0.700; SP=40.0%; PPV=15.5%). In addition, the joint discrimination ability of both miR-20b-5p and CA 19-9 (AUC=0.900) was significantly higher than the one achieved by the CA 19-9 tested alone (p=0.003). Our data suggest that plasma levels of miR-20b-5p, miR-29a, and miR-18a-5p could be useful for identifying early diabetes, albeit not as an early manifestation of PanC, and highlight miR-20b-5p as a more informative marker than CA 19-9 in distinguishing non-PanC with recent diabetes from HS without diabetes.